Psikoedukasi Manajemen Stres Pengasuhan pada Ibu di Masa Pandemi di Desa Pasirtanjung - Vinna Ramadhany Sy,; Iriani Indri Hapsari; Fitri Lestari Issom; Adhissa Qonita (Jendela Akademika, 2023)
Due to the impact of the pandemic, one of the problems that have arisen is the level of stress experienced by mothers, especially in accompanying their children full-time at home, as experienced by mothers in the Pasirtanjung area. Stressful conditions on the mother can negatively impact optimizing maternal care for children, resulting in less than optimal child development. Therefore, psychoeducation is needed to help mothers overcome stressful conditions related to parenting. This psychoeducational activity aims to provide knowledge and skills regarding parenting stress management to mothers during a pandemic in the Pasirtanjung area. With this psychoeducation, mothers can understand and manage the stress that arises in various conditions related to caring for their children so mothers can be more relaxed and more optimal in caring for their children. In addition, ifthe mother can provide optimal care, the child's development will develop optimally. We delivered psychoeducation through a presentation with question-and-answer sessions and video screenings related to stress management. Also, there was a relaxation practice so that mothers feel relaxed. The participants were 31 PKK mothers in Pasirtanjung. Data analysis used the T-test with SPSS 25.00. The results showed no differences in stress levels before and after psychoeducation. There were also no differences in understanding of parenting stress before and after stress management training in parenting. In conclusion, there was no difference in stress levels or understanding related to parenting stress before and after the implementation of psychoeducation. Education level is an essential factor that impacts participants' understanding of the material provided; thus, it needs to be adapted more to the participant's ability.